REFLECTIONS OF LAW 11.638/07 IN THE ACCOUNTING INDICATORS OF TEXTILE COMPANIES LISTED ON BM&FBOVESPA - Cunha, Paulo Roberto da (2013)
In December 2007, Law 11.638 (2007) was enacted in Brazil, which altered the Corporate Law. This law imposed significant changes, including the adoption of the Brazilian accounting standards in accordance with international standards, which implies different changes in the financial statements. According to this perception of changes in the financial statements, changes can also take place in the accounting indicators used for the purpose of financial statement analysis. In that context, in this paper, the aim is to verify whether Law 11.638 (2007) entailed statistically significant reflections in the accounting indicators. A descriptive study was undertaken with a quantitative approach. Data were collected from the Standardized Financial Statements (SFSs) for the period from 2000 till 2008, available on the website of the Brazilian Securities Commission (CVM). The convenience sample consisted of 16 companies listed on BM&FBovespa, classified in the cyclical consumption sector, in the subsector tissue, clothing and footwear, under the ply and tissue segment, with all SFSs in the period under study. Statistical linear regression techniques were applied based on the Koyck Model and the canonical correlation model. The results showed that a statistically significant canonical correlation exists between the accounting indicators in force before Law 11.638 (2007) and the accounting indicators after the same law came into force. In general, according to the companies analyzed, it is concluded that the accounting indicators underwent no statistically significant alterations as a result of the elaboration of the financial statements in compliance with the premises of Law 11.638 (2007).